"Passion" versus "patience": the effects of valence and arousal on constructive word recognition. Issue 6 (18th August 2019) - Kever, Anne; Grynberg, Delphine; Szmalec, Arnaud; Smalle, Eleonore; Vermeulen, Nicolas
ABSTRACT: Accumulating evidence suggests that emotional information is often recognised faster than neutral information. Several studies examined the effects of valence and arousal on word recognition, but yielded partially diverging results. Here, we used two alternative versions of a constructive recognition paradigm in which a target word is hidden by a visual mask that gradually disappears, to investigate whether the emotional properties of words influence their speed of recognition. Participants were instructed either to classify the incrementally appearing word as emotional or non-emotional (semantic categorisation task) or to decide whether the appearing letter string is an existing word or not (lexical decision task). Results from both tasks revealed faster recognition times for high- compared to low-arousing words, and for positive compared to negative or neutral words. These findings indicate a recognition advantage for emotionally positive and highly arousing stimuli that persists even when visual word recognition is hampered and participants are encouraged to make more active, semantic inferences to generate the meaning of the emerging word.